Intramolecular Dimerization Quenching of Delayed Emission in Asymmetric D–D′–A TADF Emitters - Woon, Kai Lin; Yi, Chih-Lun; Pan, Kuan-Chung; Etherington, Marc K.; Wu, Chung-Chih; Wong, Ken-Tsung; Monkman, Andrew P. (American Chemical Society, 2019)
Understanding the excited-state dynamics and conformational relaxation in thermally activated delayed fluorescence (TADF) molecules, including conformations that potentially support intramolecular through-space charge transfer, can open new avenues for TADF molecular design as well as elucidate complex photophysical pathways in structurally complex molecules. Emissive molecules comprising a donor (triphenylamine, TPA) and an acceptor (triphenyltriazine, TRZ) bridged by a second donor (9,9-dimethyl-9-10-dihydroacridin, DMAC, or phenoxazine, PXZ) are synthesized and characterized. In solution, the flexibility of the sp3-hybridized carbon atom in DMAC of DMAC-TPA-TRZ, compared to the rigid PXZ, allows significant conformational reorganization, giving rise to multiple charge-transfer excited states. As a result of such a reorganization, the TRZ and TPA moieties become cofacially aligned, driven by a strong dipole-dipole attraction between the TPA and TRZ units, forming a weakly charge-transfer dimer state, in stark contrast to the case of PXZ-TPA-TRZ where the rigid PXZ bridge only supports a single PXZ-TRZ charge transfer (CT) state. The low-energy TPA-TRZ dimer is found to have a high-energy dimer local triplet state, which quenches delayed emission because the resultant singlet CT local triplet energy gap is too large to mediate efficient reverse intersystem crossing. However, organic light-emitting diodes using PXZ-TPA-TRZ as an emitting dopant resulted in external quantum efficiency as high as 22%, more than two times higher than that of DMAC-TPA-TRZ-based device, showing the impact that such intramolecular reorganization and donor-acceptor dimerization have on TADF performance. © 2019 American Chemical Society.